A Theory of Competition Among Pressure Groups for Political Influence - Becker, Gary S. (Quarterly Journal of Economics, 1983)
This paper presents a theory of competition among pressure groups for political influence. Political equilibrium depends on the efficiency of each group in producing pressure, the effect of additional pressure on their influence, the number of persons in different groups, and the deadweight cost of taxes and subsidies. An increase in deadweight costs discourages pressure by subsidized groups and encourages pressure by taxpayers. This analysis unifies the view that governments correct market failures with the view that they favor the politically powerful: both are produced by the competition for political favors.